Viscous flow simulation around a moving projectile and URV. (4th August 2014) - Ng, E.Y.K.; Tan, C.K.
Using a commercial computer program, Flow–3D, two cases of three–dimensional incompressible laminar flow simulation were studied. They are the underwater projectile at various angles of attack, and an underwater vehicle at zero angle of attack. The results presented include the evaluation of drag, lift and the static pressure contours. Two different inlet velocities were used on the simulation of the projectile. The compared results agreed reasonably only with others' computation due to the fact that some parameters are unknown and because of the different numerical algorithms and approaches used by the software. Simulation was later performed on the underwater vehicle with three cylinders and four thrusters. No experimental data were available for comparison, but preliminary analysis showed that the results are logical and reasonable. Recommended future work includes the use of different angles of attack, Reynolds number and velocities. Other source codes and commercial software should also be considered to validate the results.